Stigmatization of Leprosy Patients at the Primary Hospital in North Central Timor: a Qualitative Study - Ika Febianti Buntoro; Nicholas Edwin Handoyo; Herjuni Oematan; Rusnah, Fauziyah Nadira Riani (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2025)
Background: Leprosy is a chronic bacterial infection that affects the peripheral nervous system, skin, nosend eyes and can cause disability. Clinical symptoms and disabilities can give leprosy patients a negative impression, known as stigma, which can affect their self-acceptance. Purpose: This study aims to analyze the perceptions of leprosy patients at the a primary hospital in North Central Timor regarding the stigma they experience. Methods: The study was a qualitative research, utilizing the in-depth interview method. The sampling technique used purposive sampling, applied maximum variation sampling, and involved 20 patients in the study.The interview results were transcribed and analyzed using the Open Code 4.03 program. The coding results were grouped into themes and subthemes that emerged. Result: This study found that internal and social stigma affected 80% of the 20 leprosy patients at a primary hospital. Misperceptions primarily cause internal stigma, which in turn triggers fear of infection and isolation from the community. Social stigma, also triggered by misperceptions, leprosy symptoms, and disability, leads to discrimination, and ostracism, even in family circles and places of worship. Patients experience negative impacts on their self-esteem, social life, and economy. Conclusion: Leprosy patients experience internal and social stigma, with 16 out of 20 patients affected. Misperceptions, symptoms, and disability due to leprosy are the leading causes. This stigma has far-reaching social, economic, and educational impacts. Support, education, and preventive measures are needed to overcome the stigma that worsens the condition of leprosy patients.